Evaluation of the Side Effects of COVID-19 Vaccines - Farzin Bagheri Sheykhangafshe (Shahrekord University of Medical Sciences, 2022)
The coronavirus disease 2019 (COVID-19) originated in Wuhan, Hubei province, China, and soon spread as a pandemic throughout China and many other countries until March 11, 2020.The spread of the disease worldwide was so rapid that it became the biggest public health threat in 2020.COVID-19 has a wide variety of symptoms such as high fever, dry cough, body aches, shortness of breath, and high transmission power, and it has affected the physical health and psychological states of many people in the world.The COVID-19 pandemic has caused fear, stress, and anxiety in many parts of the world.The lack of effective treatment for COVID-19 has posed a difficult challenge to all countries across the world. In this regard, several solutions were proposed, including home quarantine, social distancing, masking, closure of schools, universities, and high-risk jobs by governments to control and prevent the outbreak of COVID-19, but provided that a significant number of people around the world are vaccinated, one cannot expect the global COVID-19 pandemic to decrease dramatically. Finally, after much effort, the Food and Drug Administration licensed Pfizer- BioNTech vaccines from December 11 and Moderna from December 18. According to studies, these two vaccines are 95% effective against COVID-19 for people over 16 years of age.